Temperature-dependent relative self-absorption measurements in 27Al - Koseoglou, Pavlos; Cortés, M. L.; Isaak, J.; Werner, V.; Papst, O.; Kleemann, J.; Beuschlein, M.; Pietralla, N.; Ahmed, U.; Ide, K. E.; Jurosevic, I.; Nickel, C.; et al. (HNPS Advances in Nuclear Physics, 2022)
<span id="docs-internal-guid-062de43d-7fff-4a01-240e-bd32c6f14307" style="font-size: 11pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Nuclear resonance fluorescence measurements provide direct sensitivity to ground-state transition widths by probing the photoexcitation process of nuclear resonances. A technique in Relative Self-Absorption (RSA) measurements, in which measurements are done at multiple absorber temperatures, was developed and tested with <span style="font-size: 11pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">27<span style="font-size: 11pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Al at the Darmstadt High Intensity Photon Setup of the <span style="font-size: 12pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Superconducting Darmstadt Linear Accelerator<span style="font-size: 11pt; font-family: ’Times New Roman’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">. The advantage of this technique, over the regular RSA, is the possibility to overcome the need for theory input on the effective temperatures and the uncertainties that they introduce in the measured level widths. The technique and the preliminary results of the first test-measurements are presented in this proceedings.